Multilocus Sequence Analysis of Clinical "Candidatus Neoehrlichia mikurensis" Strains from Europe - Grankvist, Anna; Moore, Edward R B; Svensson Stadler, Liselott; Pekova, Sona; Bogdan, Christian; Geißdörfer, Walter; Grip-Lindén, Jenny; Brandström, Kenny; Marsal, Jan; Andréasson, Kristofer; Lewerin, Catharina; Welinder-Olsson, Christina; et al. (Journal of clinical microbiology, 2015)
"Candidatus Neoehrlichia mikurensis" is the tick-borne agent of neoehrlichiosis, an infectious disease that primarily affects immunocompromised patients. So far, the genetic variability of "Ca. Neoehrlichia" has been studied only by comparing 16S rRNA genes and groEL operon sequences. We describe the development and use of a multilocus sequence analysis (MLSA) protocol to characterize the genetic diversity of clinical "Ca. Neoehrlichia" strains in Europe and their relatedness to other species within the Anaplasmataceae family. Six genes were selected: ftsZ, clpB, gatB, lipA, groEL, and 16S rRNA. Each MLSA locus was amplified by real-time PCR, and the PCR products were sequenced. Phylogenetic trees of MLSA locus relatedness were constructed from aligned sequences. Blood samples from 12 patients with confirmed "Ca. Neoehrlichia" infection from Sweden (n = 9), the Czech Republic (n = 2), and Germany (n = 1) were analyzed with the MLSA protocol. Three of the Swedish strains exhibited identical lipA sequences, while the lipA sequences of the strains from the other nine patients were identical to each other. One of the Czech strains had one differing nucleotide in the clpB sequence from the sequences of the other 11 strains. All 12 strains had identical sequences for the genes 16S rRNA, ftsZ, gatB, and groEL. According to the MLSA, among the Anaplasmataceae, "Ca. Neoehrlichia" is most closely related to Ehrlichia ruminantium, less so to Anaplasma phagocytophilum, and least to Wolbachia endosymbionts. To conclude, three sequence types of infectious "Ca. Neoehrlichia" were identified: one in the west of Sweden, one in the Czech Republic, and one spread throughout Europe.
Keywords: Anaplasmataceae Infections; Švédsko; Humans; Phylogeny; lidé středního věku; Multilocus Sequence Typing; Sweden; Genes, Essential; Female; Aged; Molecular Epidemiology; RNA ribozomální 16S; Cluster Analysis; infekce bakteriemi čeledi Anaplasmataceae; senioři; lidé; Genotype; Germany; RNA, Ribosomal, 16S; molekulární epidemiologie; esenciální geny; Německo; genetická variace; Genetic Variation; ženské pohlaví; Male; Middle Aged; fylogeneze; multilokusová sekvenční typizace; Czech Republic; shluková analýza; genotyp; Anaplasmataceae; Česká republika; mužské pohlaví